If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3) * 2 = 0 Reorder the terms: (-3 + x) * 2 = 0 Reorder the terms for easier multiplication: 2(-3 + x) = 0 (-3 * 2 + x * 2) = 0 (-6 + 2x) = 0 Solving -6 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = 0 + 6 2x = 0 + 6 Combine like terms: 0 + 6 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 175m-125m+47750=50000-20m | | 2n^2-48n+288= | | -12x^2+28x=0 | | x^2-11x-12=-x^2-13x+48 | | 5x-5=x+11 | | -2(3x-4y)= | | d+6(3)=11 | | 2b+7=-36 | | 29m+4=28+13m | | 2+6h=6+3h | | 5(-8-2)+3= | | -4x+2=10 | | 7x+2+6x+8=12x+5 | | 8y+2(y-5)=5(y+1)-2 | | x^2-11x-11=-x^2-13x+48 | | -2y-15=5y+13 | | 6-4(a+1)=7+a | | -5(x-4)-26=-6 | | 15+x=31 | | -3y+3=-3(2y+6) | | 7x+3x= | | 4x^2+15x+13=0 | | 18-7y=4 | | 5x+5=-3+2x+14 | | 7x+8x-3x=1x | | 6t+4(1-4t)= | | 4t+11=19-6t | | -5(n+4)= | | 2x+2+x+11=x+2 | | 2x+2=x+11 | | y-.75=.25 | | 9+x=9 |